(untitled) (Research, Society and Development, 2022)
Introduction: Chronic kidney disease is associated with clinical and nutritional changes, resulting from the pathology itself, due to the homeostatic and metabolic changes that kidney dysfunction causes, and the treatment. Objective: To characterize the clinical and nutritional profile of patients with chronic kidney disease undergoing hemodialysis. Methodology: Descriptive, cross-sectional, quantitative, analytical and documentary study, carried out with 50 patients. Socioeconomic, demographic, clinical and biochemical data were collected, the latter being performed after hemodialysis. Subsequently, anthropometric and food consumption assessments were performed (24-hour recall). The project was approved by the research ethics committee (opinion No. 2,970,945). Results: Gender equivalence was observed, with a mean age of 57±18.8 years. The most frequent comorbidities were systemic arterial hypertension (82%) and type 2 diabetes mellitus (48%). In the biochemical evaluation, the values ​​of creatinine, hemoglobin, serum calcium and hematocrit were reduced, urea, serum potassium, ferritin and blood glucose were high. there was a prevalence of eutrophy in the analysis of body mass index (BMI) (56%) and low musculature in the analysis of arm circumference (AC). Interdialytic weight gain (IDWG) averaged 2.5% (±0.8) and was negatively related to albumin, and positively correlated with serum levels of potassium, phosphorus, calcium and dietary potassium. BMI showed a positive correlation with serum hematocrit and blood glucose levels. Conclusion: There was a change in the nutritional, biochemical and dietary status of this population, it is observed that the association between these indicators allows a more complete result on the nutritional status of chronic kidney patients, enabling the correct nutritional intervention.